Trip Home. The Tourism of the Roots and the Italian Raiz Guide - Grillo, Eduardo (E|C, 2022)
During the last decades, new types of tourism have become popular, and they defy the traditional oppositions traveler/tourist, daily/non-daily, leisure/business. Among these, it is interesting the case of roots tourism, consisting of people who travel to the land of their ancestors to establish a connection with their past. Every visit to a faraway place always has the goal of actualizing the visitor's dreams, but in this specific situation it is more about materializing the passional-interpretative background of the stories connected with one's family. Roots tourism is becoming more and more important in Italy as well. We take the case of Raiz Italiana, a young association that promotes the rediscovery of the Italian territory tied with the emigrant's descendants through the planning of tailored journeys and providing assistance during the archival research. In particular, the association publishes the guidebook Guida alle Radici Italiane: un viaggio sulle tracce dei tuoi antenati, with three volumes already printed. We propose a brief analysis of the chapter dedicated to the Calabrian region, insisting on the memorial landscape of social nature offered to the roots tourist. The chapter organizes an effective figurative path, between places, tastes, myths, and stories, to provide a regional portrait and to build a ground for an esthetic experience, in which tourists could modify themselves rediscovering their roots.